2013
DOI: 10.3390/agronomy3020404
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biochar Application on Soil Properties and Plant Growth of Pot Grown Lettuce (Lactuca sativa) and Cabbage (Brassica chinensis)

Abstract: The effect of rice-husk char (potentially biochar) application on the growth of transplanted lettuce (Lactuca sativa) and Chinese cabbage (Brassica chinensis) was assessed in a pot experiment over a three crop (lettuce-cabbage-lettuce) cycle in Cambodia. The biochar was the by-product of a rice-husk gasification unit and consisted of 28.7% carbon (C) by mass. Biochar application rates to potting medium of 25, 50 and 150 g kg−1 were used with and without locally available fertilizers (a mixture of compost, liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
137
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(166 citation statements)
references
References 22 publications
(39 reference statements)
20
137
3
6
Order By: Relevance
“…This positive effect on plant growth was also observed by Carter et al (2013), who found an improvement in lettuce and cabbage stem length after rice-husk biochar addition at 50 g.kg -1 on a sandy soil.…”
Section: Plant Growth Indicatorsmentioning
confidence: 51%
“…This positive effect on plant growth was also observed by Carter et al (2013), who found an improvement in lettuce and cabbage stem length after rice-husk biochar addition at 50 g.kg -1 on a sandy soil.…”
Section: Plant Growth Indicatorsmentioning
confidence: 51%
“…Previous research has shown that the level of PAHs in a broad suite of biochars produced using different methods and from different feedstocks does not result in biochars containing total PAH concentrations or bioavailable PAH concentrations above guideline values set by relevant biochar standards [13]. Specifically for biochars produced form rice husk, previous studies have also reported low concentration of PTEs [14] that do not exceed guideline values set by the UK for the use of sewage sludge application to soil [15]. One additional environmental issue specifically related to the addition of rice husk biochar to soil is the high amount of silicates in the biomass which may lead to the production of crisobalite, an element with associated health concerns, during the gasification process [15].…”
Section: Introductionmentioning
confidence: 98%
“…Also, biochar addition to mineral fertilizers significantly increased plant growth (Schulz andGlaser, 2012, Biederman andHarpole, 2013). The biochar treatments were found to increase the final vegetative biomass, root biomass, plant height and leaf number of lettuce and cabbage in all the cropping cycles compared to no biochar treatments (Carter et al, 2013). Furthermore, Biochar as previously mentioned is an amendment that can be used for enhancing soil moisture content which may increase the crop productivity.…”
mentioning
confidence: 94%